Tortuosity of the porous structure of carbon gels. (January 2021) - Flores-López, Samantha L.; Ramírez-Montoya, Luis A.; Casal, M. Dolores; Montes-Morán, Miguel A.; Menéndez, J. Angel; Arenillas, Ana
Abstract: Extensive studies on the correlation between synthesis variables and the final properties of resorcinol-formaldehyde carbon gels have been performed. This knowledge allows us to obtain carbon gels with analogous mean pore sizes and porosity from different combinations of synthesis variables. However, although the materials exhibit these similar characteristics, their behaviors may be very different in certain applications. Since the distribution and connectivity of the polymeric clusters are strongly affected by variables such as the amount of water and methanol in the precursor solution, it seems that the pore tortuosity and thus the permeability of the materials are also dependent on these factors. Further analysis of a series of carbon gels with the apparent same porosity shows how an increase in the amount of water or a suitable combination of methanol content and the pH of the precursor solution used for the polymerization process generate less tortuous pore structures. This allows us to attain even finer tuning of the porous structure of RF carbon gels either to reduce pressure drop or to increase the residence time of solutes in separation processes. Graphical abstract: Image 1